Optical Sensing and Detection VI 2020
DOI: 10.1117/12.2556799
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering and rheological effects in an optical fibre coupled nanoparticle suspension

Abstract: This study forms the first part of research into enhancing the forward and back scattering of light in an optical fibre using nanoparticles (NPs). This approach has the potential to enhance the sensitivity of optical fibre sensing by increasing the signal-to-noise ratio. The work described in this paper is focused on understanding the scattering of light by a suspension of NPs in refractive index matching liquid. It was noted early in the experimental work that rheological effects related to the viscosity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, it is not easy to transfer gold NPs to refractive index liquid. In our former work [18], we tried to transfer commercial gold NPs suspension in citrate buffer (Sigma Aldrich) to refractive index liquid (Cargille). The experimental results showed that the transferring process is not efficient enough.…”
Section: Case Study With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not easy to transfer gold NPs to refractive index liquid. In our former work [18], we tried to transfer commercial gold NPs suspension in citrate buffer (Sigma Aldrich) to refractive index liquid (Cargille). The experimental results showed that the transferring process is not efficient enough.…”
Section: Case Study With Experimentsmentioning
confidence: 99%
“…In practice, manufacturing optical fibres with NPs is not easy in an optical laboratory and a careful design is needed. In order to investigate the behaviours of NPs in fibre optic sensors, we proposed a simple setup to investigate the characteristics of NPs for further development in SHM [18]. It is to drop refractive index (RI) matching liquid between two optical fibre tips and to study the scattering characteristics for different NPs under different experimental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not easy to manufacture NP-doped optical fibres to test different designs in the an optical laboratory. To overcome this problem, we used the method of dropping refractive index matching liquid containing gold NPs at the optical fibres end tips to investigate the intensity change of the scattered light from the interfaces in our previous work 9 and intend to build on this relationship in the light scattering between the optical fibre end tips and in the optical fibre itself in order to recover the scattered light signal in the optical fibre containing NPs. Although refractive index liquid can have a good refractive index match with the optical fibre, traditional optical fibre sensors used for SHM are solid sensors rather than liquid sensors.…”
Section: Introductionmentioning
confidence: 99%